The Effect of Students’ Perception on School Environment and Self-discipline towards Their Achievement in Learning English: A Survey at a Private Vocational School in Bogor - Prasetya, Eska Perdana (ENGLISH JOURNAL, 2016)
This study was aimed at identifying the correlation between students’ perceptions on school environment and self-discipline towards their achievement in learning English. By employing a questionnaire as the main instrument used to gain its data, the method of this study was survey. SPSS was mainly employed to do data analysis. The result shows that there is a significant correlation between the students’ perceptions on school environment and self-discipline towards their achievement in learning English.